The Influence of Cooperative Learning Model Student Team Achievement Division ( STAD) And Learning Motivation On Learning Outcomes - Yuliastuti, Yayuk Harini; Degeng, I Nyoman Sudana; Leksono, Ibut Priono (STAI Miftahul Ula Nganjuk, 2023)
The purpose of this research is to find out 1). Differences in learning outcomes in Geography subject between students who were given the Student Team Achievement Division (STAD) learning model and those who were given Snowball Throwing learning student XI IPS class at SMAN 1 Lamongan and SMAN 1 Sukodadi . 2). The difference in the learning outcomes of students who have high learning motivation and low learning motivation in Geography 3 ). There is an interaction between the application of the Student Team Achievement Division (STAD) learning model and Snowball Throwing with Geography Learning Motivation on Learning Outcomes eye lesson geography . This research involves two independent variables, one moderator variable, and in the measurement (post test) there is one variable that is measured. The independent variable in this study is the learning model which consists of STAD cooperative learning and the Snowball Throwing learning model. The moderator variable is learning motivation which is divided into high motivation and low motivation. While the dependent variable is the result student learning . Calculation results Anava 2 lanes known , that 1). probability score the significance of the learning model variable ( between the STAD – Snowball Throwing learning models ) is 0.000. this means significance not enough of 0.05 (P < 0.05), Mean exist _ difference results Study eye lesson geography between given students learning the Student Team Achievement Division (STAD) model with those who are given Snowball Throwing learning model . 2). Value probability the significance of the variable motivation Study of 0.000. this means significance not enough of 0.05 (P < 0.05), that is There is difference results Study eye lesson geography between students who have motivation Study height and students who have motivation Study low . 3). score probability significance on learning model variables and motivation Study of 0.005. this means significance not enough from 0.05 (P < 0.05), so H 0 rejected and H 1 accepted . With thereby can concluded , that There is interaction between application learning model Student Team Achievement Division (STAD) and Snowball Throwing with motivation Study student to results Study